Occupational stressors and work accidents among health workers - Mariana Rabelo Gomes; Tânia Maria de Araújo; Jorgana Fernanda de Souza Soares; Camila Carvalho de Sousa; Iracema Lua (Universidade de São Paulo, 2021)
ABSTRACT OBJECTIVE To test the association between occupational stressors and work accidents due to exposure to biological material (ATbio) in health workers, considering the isolated and combined analysis of the dimensions of two models, the demand-control model (DCM) and the effort-reward imbalance model (ERI). METHODS Cross-sectional study in a representative sample of workers with higher, technical and secondary education, including health agents from primary and medium-complexity care units in five cities in Bahia. Random sampling was selected, stratified by geographic area, level of service complexity and occupation. The outcome variable was ATbio; The main exposure was occupational stressors, assessed by the DCM and ERI. Incidences and relative risks were estimated as a function of the acute, short-term nature of the outcome of interest. Associations between ATbio and isolated and combined DCM and ERI dimensions were tested. RESULTS A total of 3,084 workers participated in the study. The global incidence of ATbio was 3.4% and was associated with high psychological demand, high effort and high commitment to work, adjusted for sex, age, education and work shift. High-strain work and a situation of imbalance between efforts and rewards were associated with ATbio. With the combination of the models, an increase in the measure of association with the outcome was observed. Significant associations of greater magnitude were observed in the complete combined models. ATbio's risk was 5.23 times higher among those exposed in both complete models compared to the absence of exposure in both models. CONCLUSIONS Occupational stressors were associated with ATbio. Advantages in using the combined models were observed. The approach of different psychosocial dimensions has expanded the ability to identify exposed groups, offering a solid basis for interventions for ATbio's prevention in health.